Avaliação e comparação da resistência à corrosão por pites do aço superaustenítico AL 6XN PLUS ™ e dos aços inoxidáveis austeníticos da série AISI 304L, 316L e 317L - Cardoso, Jorge Luiz (2011)
The oil distillation towers routinely suffer problems related to corrosion due to the high level of acidity present in the oil requiring a high resistance to corrosion of the equipment in use. Among the materials used in the manufacturing and coating of equipment, we highlight the Austenitic Stainless Steel of the 300 Series. Austenitic stainless steels are widely used in components for high temperatures, such as boilers, super heaters, chemical reactors, etc. Super austenitic stainless steels, due to their high Cr and Mo content, as compared to regular austenitic types, show a higher resistance to pitting corrosion, which is one of the most harmful forms of localized corrosion. These steels have been pointed as a possible replacement for common austenitic steels for applications at high temperatures and aggressive media, as in the oil industry. In order to evaluate and compare the resistance to pitting corrosion of AL 6XN PLUS ™ super austenitic stainless steel commercial with the 304L, 316L and 317L austenitic stainless steels for high temperatures, samples of these steels were subjected to heat treatments at temperatures of 500, 700 and 900 ° C for a period of 72 hours. Samples in the as-received condition were also analyzed. Cyclic polarization tests were performed to evaluate and compare the resistance to pitting corrosion of the materials mentioned using an aqueous solution of sulfuric acid and sodium chloride concentrations in 0.5 M H2SO4 + 0.5 M NaCl and 1 M H2SO4 + 2 M NaCl. The results showed a higher susceptibility to pitting corrosion in the 304L steel. 316L and 317L steels showed intermediate performance (smaller pits as the material became more noble) and crevice corrosion as well. The AL 6XN PLUS ™ super austenitic steel showed the best performance in both electrolytes used. Only a sample of the super austenitic steel and in an extreme condition of temperature and corrosive environment showed susceptibility to pitting corrosion. This behavior is very desirable in the oil industry.